Hyperoside induces ferroptosis in chronic myeloid leukemia cells by targeting NRF2 - Junyi Wei; Quanyou Chai; Yuqiao Qin; Long Li; Chunling Guo; Zhaoyang Lu; Huimin Liu (BMC, 2024)
Abstract Background Hyperoside (quercetin-3-O-β-D-galactopyranoside) is a flavonol glycoside compound derived from plants in the Hypericum and Crataegus genera that reportedly exhibits an array of anti-inflammatory, antioxidant, and antitumor properties such that it has been used to treat various diseases. Whether it can serve as an effective treatment for chronic myeloid leukemia (CML) cells, however, has yet to be established. The present study was thus devised to assess the therapeutic effects of hyperoside on CML cells and to clarify the underlying mechanism of action. Methods Cellular viability, proliferative activity, migration, and apoptotic death were respectively analyzed through CCK-8, EDU, transwell, and flow cytometry assays. RNA-seq and bioinformatics approaches were further employed to evaluate the mechanisms through which hyperoside influences CML cells, while analyses of reactive oxygen species (ROS) and free iron were detected with commercial kits. Transmission electron microscopy was used to assess mitochondrial morphology. Molecular docking, cellular thermal shift assay (CETSA), and drug affinity responsive target stability (DARTS) approaches were also used to explore the ability of hyperoside to target NRF2. Results From a mechanistic perspective, hyperoside was able to inhibit SLC7A11/GPX4 signaling in a manner that was abrogated by the ferroptosis inhibitor ferrostatin-1. NRF2 was also closely associated with the inactivation of the SLC7A11/GPX4 axis mediated by hyperoside such that overexpressing NRF2 ablated the benefits associated with hyperoside treatment. Conclusions The present analyses indicate that hyperoside can target the NRF2/SLC7A11/GPX4 axis to induce ferroptotic CML cell death.